Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4309/jgi.2018.39.8
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Disorder in the College Student-Athlete Population: An Overview

Abstract: This review examines research from 1991 to the present regarding college student-athlete gambling addiction and disorder issues, with an emphasis on prevalence rates, motivations, and comorbid disorders, as well as National Collegiate Athletic Association (NCAA) national studies and derivative research. Subsets of the college student-athlete population, specifically minority athletes, are also examined. Databases PsycINFO, PsycARTICLES, ERIC, SPORTDiscus, MEDLINE, and Dissertation Abstracts International (ProQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Previous research reports mixed findings regarding whether college student-athletes gamble more frequently or have more gambling-related problems than non-athletes (Stuhldreher et al, 2007;Weinstock et al, 2007), with a recent review indicating that student-athletes have higher rates of pathological gambling than non-athletes although they report similar rates of gambling engagement (Nowak, 2018). Based on previously identified rates of past year gambling among a general population of college students (Barnes et al, & Tidwell, 2010;Blinn-Pike et al, 2007;Lostutter et al, 2014), student-athletes in the present study appear to have significantly lower rates of past year gambling participation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reports mixed findings regarding whether college student-athletes gamble more frequently or have more gambling-related problems than non-athletes (Stuhldreher et al, 2007;Weinstock et al, 2007), with a recent review indicating that student-athletes have higher rates of pathological gambling than non-athletes although they report similar rates of gambling engagement (Nowak, 2018). Based on previously identified rates of past year gambling among a general population of college students (Barnes et al, & Tidwell, 2010;Blinn-Pike et al, 2007;Lostutter et al, 2014), student-athletes in the present study appear to have significantly lower rates of past year gambling participation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that several factors predispose adolescents to problem gambling among which are socio-demographic and environmental influences. Demographic characteristics such as young age, male gender, being employed, and not being religious have been associated with problem gambling in this population (Abdi et al, 2015;George et al, 2016;Hoffman, 2000;Matama, Mbago, & Ngoboka, 2021;Nowak, 2018). Furthermore, extant studies have reported specific socio-cultural factors including peer gambling, parental gambling, and societal perception on gambling as being associated with problem gambling (Freund et al, 2019;Keatley et al, 2019;Matthew et al, 2021;Riley et al, 2021).…”
Section: Introductionmentioning
confidence: 93%